Strategi Pemetaan Mutu Pendidikan Berbasis Sistem Penjaminan Mutu Internal pada Balai Penjaminan Mutu Pendidikan Yogyakarta - Maqhfira Agustin, Nadilla Aleyda; Lailatur Rohmah; ⁠Faidhur Rohim; ⁠Susi Anto; Dody Arianto (Indonesian Journal of Action Research, 2026)
Purpose – This article aims to formulate an education quality mapping strategy based on the Internal Quality Assurance System (SPMI) at the Balai Penjaminan Mutu Pendidikan (BPMP) D.I. Yogyakarta. The focus is directed at how quality mapping can function as an instrument for decision-making, advocacy, supervision, and facilitation of data-based education service improvement. Design/methods – This article uses a qualitative approach based on document study. The main sources consist of SPMI cycle documents, the 2026 PMP activity design of BPMP D.I. Yogyakarta, product knowledge of the 2025 Education Report Card data, and policy materials for improving education quality in D.I. Yogyakarta in 2026. The data were analyzed through content categorization based on the SPMI cycle, the Identification-Reflection-Improvement framework, and the relationship among indicators of the National Education Standards. Findings – The analysis shows that quality mapping needs to be positioned as a continuous improvement cycle, not merely as a data collection activity. This strategy includes standard setting, integration of internal and external data, identification of low or moderate achievements, tracing root causes through the eight National Education Standards, formulation of solution recommendations, and integration of mapping results into KSP, RKJM, RKT, RKAS, and ARKAS. The 2026 agenda of BPMP D.I. Yogyakarta demonstrates a strategic workflow through quality mapping, mapping of potential model schools, partnership facilitation, supervision, monitoring, and evaluation. The contribution of this article is a quality mapping strategy model based on SPMI that integrates the quality cycle, Education Report Card platform, and education planning documents.